Marketing of Skipjack Tuna (Katsuwonus pelamis) in Lappa Island, Sinjai Regency - Bahar, Annisa; Adhawati, Sri Suro; Tahang, Hamzah; Hasani, M. Chasyim; Fakhriyyah, Sitti (PONGGAWA : Journal of Fisheries Socio-Economic, 2025)
This study aims to determine the marketing channels of Skipjack Tuna (K.pelamis) in TPI Lappa, Sinjai Regency and to analyze the costs and marketing margins of Skipjack Tuna (K.pelamis) in TPI Lappa, Sinjai Regency, and to determine the efficiency of marketing Skipjack Tuna (K.pelamis) in TPI Lappa, Sinjai Regency. This research was conducted in February - March 2025. The method of determining the location was chosen intentionally (purposive) with the consideration that the North Sinjai District has several villages that are coastal areas, especially in TPI Lappa Sinjai, most of whose residents work as fishermen and the area has characteristics that are in accordance with the objectives of the study. The type of research used is a type of research using a quantitative and qualitative approach with a population sampling method. Data collection techniques are observation, interviews, literature studies, and documentation. The results of this study are that there are four marketing channels at TPI Lappa. Also, the results of the highest marketing margin are in the fourth marketing channel, which is IDR 25,000 with a marketing cost of IDR 7,846/kg, a profit of IDR 15,878/kg, so that efficient marketing is obtained at <1%.